Cardiorespiratory evaluation of juvenile rats experimentally envenomed with Tityus serrulatus venom - MCL Pinto; MB Melo; ML Cruz; D Verçosa Junior; MM Melo (Journal of Venomous Animals and Toxins including Tropical Diseases, 2010)
Accidental envenomation caused by Tityus serrulatus scorpions is very common in Brazil and may result in serious cardiorespiratory alterations that are frequently fatal to children. In the present study, the effects of T. serrulatus venom on the cardiorespiratory system of recently weaned male Wistar rats were evaluated. Fifteen animals were distributed into three groups (n = 5). The control group A received 400 μL ultrapure water by subcutaneous injection, while the experimental groups B and C were injected with scorpion venom (100 and 450 μg, respectively, in 400 μL water). Electrocardiogram (ECG) traces were obtained prior to the experiment, at five-minute intervals up to 30 minutes after treatment. At 40 minutes after envenomation, the animals had severe acute symptoms and were subsequently anesthetized for blood collection by means of intracardiac puncture. Biochemical profiles for the cardiac muscle were established by colorimetric analysis of creatine kinase (CK) and CK-MB isoenzyme. Semiquantitative analysis of troponin was performed using the immunochromatographic assay. Following euthanasia, the lungs and hearts were removed and subjected to histopathological examination. All experimental animals had ECG alterations compatible with electrolytic imbalance, myocarditis and alterations of the cardiac conduction system. Envenomed animals had accentuated bradycardia at 25 and 30 minutes after venom inoculation. All experimental animals had myocardial lesions, which were confirmed by increased serum levels of CK and CK-MB, although there were no alterations in the serum concentration of troponin. Pulmonary hemorrhage was detected in whole lungs and microscopically confirmed by the presence of congested capillaries and erythrocytes in the alveolar parenchyma. In conclusion, T. serrulatus venom caused great cardiorespiratory damage to weaned rats.